High skills/giftedness and visual impairment: twice special educational need - Rosemeire de Araújo Rangni; Ailton Barcelos da Costa (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
Special Education in Brazil has historically been shown to care for individuals with disabilities. The students with high potential are in the schools, but with little visibility and recognition. It's concluded because the students in conditions of high abilities/giftedness and disability are less contemplated by special services. This paper aims to revise publications about the twice special educational needs (TSEN), talent and visual impairment, in 2002 to 2012, as well as to consider concepts about talent and visual impairment and also to reflect about TSEN. The Bibliographical and Documental methods were used. For this, it was proceeded searches in specialized books, Brazilian educational documents, and papers published in periodic. The results were: in eight papers searched only three ones were considered relevant for the research purpose. The majority of the papers available in the sites weren't in the complete form presenting only the abstract. It was revealed that there is scarce research about the thematic in Brazil, specifically, about high abilities/giftedness and visual impairment because it wasn't found any works in the Portal de Periódicos da CAPES (Coordenação de Aperfeiçoamento de Pessoal de Nível Superior). It is waited with this paper to contribute for the students with TSEN are recognized, in fact, by their high potential.